2014
DOI: 10.1176/appi.ps.201400067
|View full text |Cite
|
Sign up to set email alerts
|

State Mental Health Policy: Building a Successful Public-Academic Partnership to Support State Policy Making

Abstract: This column describes a partnership between the Maryland Mental Hygiene Administration (MHA) and the Division of Psychiatric Services Research, Department of Psychiatry, University of Maryland School of Medicine, that has implemented several evidence-based and emerging practices, such as supported employment, family psychoeducation, assertive community treatment, treatment for co-occurring mental and substance use disorders, and services for transition-age youths. The public-academic partnership has also creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…Public care agency leaders and academic researchers in PAPs declining and terminated perceived a low level of alignment in the context. This echoes the findings from studies focused on PAPs in other fields, such as public health insurance [ 31 ], environmental health [ 32 ], health care delivery [ 30 ], child welfare and mental health services [ 10 ], and general and adult mental health care [ 2 , 4 - 6 , 37 ] in which successful PAPs were reported to have aligned structure, goals, and agenda-setting process.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Public care agency leaders and academic researchers in PAPs declining and terminated perceived a low level of alignment in the context. This echoes the findings from studies focused on PAPs in other fields, such as public health insurance [ 31 ], environmental health [ 32 ], health care delivery [ 30 ], child welfare and mental health services [ 10 ], and general and adult mental health care [ 2 , 4 - 6 , 37 ] in which successful PAPs were reported to have aligned structure, goals, and agenda-setting process.…”
Section: Discussionsupporting
confidence: 69%
“…For example, local US public health departments that formally partner with academic institutions are more likely than those not engaged in partnership with academic institutes to make evidence-based policy making and implement evidence-based interventions in health care delivery [ 1 ]. Previous studies have demonstrated the important role of PAPs in training service providers [ 2 - 5 ], supporting the implementation of promising evidence-based practices [ 3 - 7 ], and conducting systems evaluation that inform policy development and program planning [ 2 , 4 ]. Such partnerships have effectively responded to the need for additional, more diverse, and more inclusive mental health and child welfare services [ 2 , 3 , 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAPs are vital to improve the health and well-being of vulnerable populations [8-11]. PAPs seek to bridge the historic divide and disconnect that has evolved among researchers and policymakers and improve the degree to which the knowledge generated by researchers is utilized for the benefit of the individuals being served by the public care sector [12,13]. A critical means through which PAPs accomplish this aim is the use of research evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that PAPs can effectively promote PAP leaders’ use of research evidence in improving youths’ outcomes [12,20,10]. However, the existing literature has not yet informed the specific mechanisms of PAPs that promote PAP leaders’ use of research evidence in improving youths’ outcomes; whether and how PAP leaders’ use of research evidence evolves along the PAP life cycle; and whether PAP partners’ concordant perceptions of usefulness of their PAP has an impact on PAP leaders’ use of research evidence.…”
Section: Introductionmentioning
confidence: 99%